Navigating Legal Barriers: The Impact of Foreign Subsidies Regulation on Chinese SOEs in EU Public Procurement - Si, Tongle (Faculty of Law, Sriwijaya University, Indonesia, 2025)
The EU Foreign Subsidies Regulation (FSR), effective from July 2023, aims to create a level playing field in the EU internal market by addressing concerns about non-EU companies gaining unfair advantages through subsidies from their home countries. By granting the European Commission extensive investigative powers, particularly in public procurement and mergers, the FSR aims to ensure fair competition and fill regulatory gaps in the EU’s existing legal framework. However, the regulation’s impact on the participation of non-EU companies in the EU public procurement market remains insufficiently explained. This article examines the impact of the FSR on non-EU companies, focusing on its effects on public procurement, especially case studies from the Commission’s investigations into two Chinese state-owned enterprises (SOEs). It offers a detailed interpretation of the FSR’s rules on foreign subsidies in the context of EU public procurement from both procedural and substantive perspectives. Additionally, the article provides practical recommendations for non-EU companies seeking to navigate the FSR's requirements and minimise its negative impacts while maintaining their participation in EU public procurement markets.